Participation rate in cervical cancer screening in general practice related to the proximity of gynecology care facilities: A 3 year follow-up cohort study - Quersin, François; Serman, Fanny; Favre, Jonathan; Rochoy, Michaël; Descamps, Axel; Gers, Elise; Duhamel, Alain; Collins, Claire; Deken-Delannoy, Valérie; Berkhout, Christophe; Raginel, Thibaut (Frontiers in Public Health, 2022)
Cervical cancer screening (CCS) by Pap tests is mainly performed by gynaecologists in France, but also by general practitioners (GPs). The screening rate is insufficient to reduce the incidence of cervical neoplasms. Our aim was to investigate the association between screening rates in patients listed with GPs and the distance between GPs’ offices and gynaecology facilities. The population of 345 GPs, and their 93,918 female patients eligible for screening over three years (2013 to 2015), were derived from the Health Insurance database. We estimated the socioeconomic level of the geographical area of GPs’ offices using the European Deprivation Index (EDI). The proximity of gynaecology facilities was calculated by computing their distance from GPs’ offices (in order to adjust the proximity of gynaecology facilities with EDI and performance of smears by the GP). The number of gynaecologists within 5 km of GP’s offices was associated with the CCS rate increasing by 0.31% for every unit increase in the density of gynaecologists within 5 km (p<0.0001). The proximity of gynaecology facilities was not significantly associated with screening rates when the GP’s office was in a deprived area. The close proximity of gynaecology facilities increased GP screening rates, except for in deprived areas.